uji UJI AKTIVITAS ANTIDIARE EKSTRAK ETANOL DAUN MENGKUDU (Morinda citrifolia L.) TERHADAP MENCIT GALUR BALB/C YANG DIINDUKSI BAKTERI Salmonella sp. - Rahmi Muthia; Yaumi Musfirah; Septiyani Candrakirana (Borneo Journal of Pharmascientech, 2019)
Morinda citrifolia are known to contain tannin active substances as antidiarrheal and anthraquinone as antibacterial. This study aims to determine the optimal activity and dose of ethanolic extract of Morinda as antidiarrheal induced by Salmonella Sp. Mus musculus divided into 5 groups consisting of 5 mice; control group (CMC-Na 0.5%), the extract group (doses 150, 300, and 600 mg / kgBW) and Diapet NR group (1.3 mg / kgBW). Each group was induced Salmonella sp 1 ml orally. Thirty minutes after induction, the group was given oral treatment and observed the onset of diarrhea, duration of diarrhea, frequency of diarrhea, fecal weights and antidiarrheal effects for 5 hours. The results showed the best decrease of diarrhea onset was EEDM 600 mg / kgBW (51.8 ± 6.53 min), the shortest diarrhea duration was also showed EEDM 600 mg /kg BW (48.8 ± 33.49 min), and the best decrease of diarrhea frequency was EEDM 300 mg /kgBW (7.4 ± 1.67 times). The best decrease of faecal weight was EEDM 300 mg /kgBW (0.416 ± 0.175 gram) and the last parameter antidiarrheal effect was also showed EEDM 300 mg / kgBB (43.10%). The conclusions of this study was EEDM has antidiarrheal activity induced by Salmonella sp bacteria when compared with control and Diapet NR, and EEDM 300 mg / kgBW is the optimal dose that given antidiarrheal effects